The Factors Influencing Sustainable Performance Among Generation Z Employees at Four-Star Hotels in Cibubur. - Anjarwani, Puspita; Emilisa, Netania; Pasha, Nabeel Ariq; Yuwono, Ikhwanul Walya; Febrianto, Ariq Dwi (Universitas Pamulang, 2025)
The growth of the hospitality industry in the Cibubur area demands improved human resource quality, particularly among Generation Z employees who now form an important segment of the workforce. This study aims to analyze the effect of green human resource management on sustainable performance, with creativity and exploratory green innovation as mediating variables. A quantitative method was employed using an explanatory research design involving 130 Generation Z employees from four-star hotels in Cibubur. Data were collected through a Likert-scale questionnaire (1–5) and analyzed using Structural Equation Modeling. The results show that green human resource management positively influences creativity and exploratory green innovation, and directly enhances sustainable performance. Additionally, creativity and exploratory green innovation partially mediate the relationship between green human resource management and sustainable performance. These findings emphasize that green human resource practices can optimize sustainable performance when accompanied by strengthened creativity and exploratory green innovation in line with the needs of the modern hospitality industry. Thus, implementing green human resource management not only supports operational efficiency but also reinforces creative, innovative, and environmentally oriented behavior, thereby increasing hotels’ sustainable competitiveness. This practice also fosters a more adaptive, collaborative, and responsive work culture in addressing the evolving sustainability demands within today’s hospitality sector.